Delirium - Oliver, Lauren, 1982- (New York : HarperCollins, 2011)
Lena looks forward to receiving the government-mandated cure that prevents the delirium of love and leads to a safe, predictable, and happy life, until ninety-five days before her eighteenth birthday and her treatment, when she falls in love.
Keywords: Love stories; Government, Resistance to -- Fiction; Families -- Maine -- Fiction; Orphans -- Fiction; Science fiction; Love -- Fiction; Government, Resistance to -- Fiction; Family life -- Maine -- Fiction; Orphans -- Fiction; Science fiction; Maine -- Fiction